Memberikan Pelatihan Motivasi Leadership dan Attitude kepada Siswa-siswi Tingkat Akhir SLTA Aliyah Pesantren Pondok Darul Qur’an Lantaburo - Pawenary, Pawenary; Muniroh, Muniroh; Suwandi, Arief; Shalsabilla , Salsyah; Pandiangan, Ima Sari; Lestari , Novita Indri; Rifqy, Ananda Aliffia; Ramadani , Hidayat (UII, 2025)
From the results of initial observations in the field so far, it can be observed that the majority of students at the Darul Qur'an Lantaburo Islamic Boarding School are more oriented towards the mission of providing quality education that integrates religious knowledge and general knowledge. It is known (1) lack of mental readiness, (2) soft skills deficit, (3) lack of leadership motivation, and (4) lack of awareness of the importance of attitude. Meanwhile, the vision and mission of developing morals and encouraging students to be active in social activities is still lagging behind. The implications of this reality are that the author is still concerned about this phenomenon. The output targets of this service include training services in the form of information related to increasing motivation, leadership and attitude. Through the service activities that have been carried out, three things have been improved, namely increasing knowledge about motivation, deepening how to become someone who has leadership and increasing knowledge about the importance of implementing a good attitude. The methods used are lecture, discussion and question and answer methods. The result of implementing this community service activity is to provide increased understanding of motivation, leadership and attitude.